Archeology, stone tools and RIMAPS technique A quantitive characterization of use - wear traces - Pal, N.; Alvarez, M.R.; Briz, I.; Dominguez, A.; Favret, Eduardo Alfredo (Microscopy Society of America, 2020)
Archaeology relies on material remains to attain a broad comprehensive understanding of humanevolution, creating undeniable challenges to the methodological field. Microscopy and image techniques have had a paramount role in this field of research since they provide different analytical lines to solve problems related to human tools. One of these problems entails to identify how a lithic tool was used. It is known, following the Russian researcher Sergei Semenov, that different working processes leave singular traces on the surface of a stone tool incontact with the working material [1]. The search of quantitative variables that allow characterizing these traces has been an important aimsince the beginning of the use-wear method with different degrees of success [2]. Despite of the limitations of the methods applied, most of them showed differences on lithic tools roughness and texture according to the worked material. Following this line of research, we applied Rotated Image with Maximum Average Power Spectrum (RIMAPS) technique in order to detect patterns that characterize the structural modifications that occur on stone tool as a result of its use [3]. RIMAPS is a novel characterization technique that allows revealing the orientation and characteristics of the topographic pattern of a surface.